Pemikiran Muhammad Nāşiruddīn al-Albāniy Tentang Jilbab dan Cadar Wanita Muslimah - Hidayatulloh, Haris (Religi, 2012)
Abstract In Islam, the veil was the emphasis function to close the genitals, which cover certain body parts that are considered vulnerable and can lead to defamation. Islam requires that women must cover their body in association with men who are legally not include relative. Vast amount of literature to review the issue headscarf Muslim women with a variety of approaches from different intellectual backgrounds. For al-Albāniy discussion about Muslim women the veil is very important because it has a lot of Muslim women who are in fact deceived by the European civilization. The Muslim is finally preening by the first and reveal ignorance of their limbs before they were ashamed to show it. This phenomenon is pushing al-Albāniy to conduct a serious study on the Islamic headscarf in accordance with the Shari´a. So that Muslim women have a clear grip on the clothing in accordance with the intent syar´i, although some terms are not absolute, he made ​​only for the Muslim woman. Similarly, the veil issue, he asserts that the veil is not obligatory but sunna. And women who wear the veil means he has followed the path of the Prophet´s wives. Keyword: Jilbab, Cadar